Research note: Ecosystem Health (EH) assessment of a rapidly urbanizing metropolitan city region of eastern India – A study on Kolkata Metropolitan Area - Das, Manob; Das, Arijit; Mandal, Ashis (Landscape and urban planning, 2020)
[Display omitted] •Ecosystem Health (EH) of a rapidly urbanizing metropolitan city of Eastern India was assessed since 2000 to 2019.•Ecosystem health was assessed using VOR model in Kolkata Metropolitan Area (KMA) since 2000 to 2019.•EH declined from 0.627 to 0.377 since 2000 to 2019.•Relatively well status of EH was decreased from 73% to 52%.•The outcome of the study may be helpful for policymakers in developing measures for eco-environmental management. Assessment of ecosystem health (EH) in Indian megacities is urgently required where ineffective environmental protection policies turned them into hotspots of a bundle of eco-environmental problems. In this study, the classic Vigor-Organization-Resilience (VOR) framework was employed to devise the ecosystem health index (EHI) of Kolkata megacity which is similar to the work of Peng et. al. (2015). Results show that EH of this megacity city region was rapidly deteriorating trend, from 0.627 to 0.377 with strong spatial heterogeneity. In 2000, areal coverage of EH status of relatively well was 73.10% reduced to 52.00% and areal coverage of weak EH status increased to 21.80% in 2019. The relatively weak and weak status of EH are concentrated in Kolkata, Howrah and its adjacent areas. The study proposed a new improvement and deterioration index to track the changes of EH at the city scale to overcome the limitation of the percentage change method. Ultimately the outcome of the study provides a better understanding of EH in Kolkata megacity region that is helpful for policymakers in developing measures for eco-environmental management.